Deus and God，the Dilemma and Reflection of the Interculture Contact - GAO, Xing (Journal of Research for Christianity in China (JRCC), 2025)
The Chinese Rites Controversy includes two parts: the issue of the Translated Name and the issue of Rites. The former focuses on what vocabulary in Chinese can be used to express the concept of "Deus", the supreme God of Christianity, and thus deduces the various dilemmas in the process of cultural concept transplantation. The latter discusses whether Chinese Catholics based on the traditional ancestor worship rituals, and whether such rituals are tolerated by Christian theological concepts. Since rites is never just a cultural issue, it not only has the effect of social norms, but also contains information about power. Therefore, this article selects only the relatively pure cultural dispute in The Chinese Rites Controversy, that is, the problem of the Translated Name, thinking about the dilemma of intercultural contact. This article will demonstrate that Matteo Ricci and Niccolo Longobardi, the representatives of two typical opposing views on the problem of name translation, actually have no real confrontation, but face two dilemmas of cultural contact: language dilemma and ontological dilemma; between them The differences between the two seem to be aimed at the "technical aspect" of the translated term, but in fact it involves many ontological issues in the process of dialogue between different cultures.